Corporate Social Responsibility of European Retail Chains in Poland - Grażyna ŚMIGIELSKA (Revista de Management Comparat International)
The article reviews the core conceptual aspects of the corporate social responsibility as a principle of business viability, and then focuses on the relevant practices adopted by major international retail chains operating on the Polish market. The empirical background consists of fact-based accounts, drawn from either corporate websites or retail companies' reports, with a view to generating a kaleidoscopic "rich picture" of current practices. The main conclusions include: the sharp increase in public's and authorities' sensitivity towards social responsibility in business, the switch from external pressure to self-commitment of retail companies in pursuing relevant actions, and the concern towards fitting measures taken in this respect into corporate strategies, also adapting them to peculiarities of Polish market.